2010
DOI: 10.1103/physrevb.82.193410
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetic moment enhancement of nickel nanoparticles embedded in multiwalled carbon nanotubes

Abstract: We report a giant magnetic moment enhancement of ferromagnetic nickel nanoparticles (11 nm) embedded in multi-walled carbon nanotubes. High-energy synchrotron x-ray diffraction experiment and chemical analysis are used to accurately determine the ferromagnetic nickel concentration. Magnetic measurements up to 900 K show an intriguing result-the saturation magnetization of the nickel nanoparticles embedded in the multi-walled carbon nanotubes is about 3.4 times as much as the value expected from the measured ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Other magnetic parameters can be influenced by the cavity‐confinement. In this regard, Zhao and co‐workers reported an increase of the magnetic moment of confined Ni MNPs by a factor of 3.4(±1.0) 84. Few years later, the same group reported an enhancement of the magnetic moment of encapsulated Fe and Fe 3 O 4 in MWCNTs also by a factor of three 85.…”
Section: “Magnetic” Synergies Between Cnts and Mnpsmentioning
confidence: 93%
“…Other magnetic parameters can be influenced by the cavity‐confinement. In this regard, Zhao and co‐workers reported an increase of the magnetic moment of confined Ni MNPs by a factor of 3.4(±1.0) 84. Few years later, the same group reported an enhancement of the magnetic moment of encapsulated Fe and Fe 3 O 4 in MWCNTs also by a factor of three 85.…”
Section: “Magnetic” Synergies Between Cnts and Mnpsmentioning
confidence: 93%
“…The incident wave Equation (7) relates to the state with the momentum p i and S i , and the scattered wave Equation (8) relates to p f and S f , respectively. The incident wave function is normalized by the unit current density and the scattered wave function is normalized by the delta function [11].…”
Section: Probabilities Of Spin-dependent Scattering By Nanomagnetsmentioning
confidence: 99%
“…Their physical properties have recently been studied experimentally, theoretically, and by computer simulation in [4][5][6][7][8][9]. The interaction between anomalous magnetic moment of the nanomagnet and the magnetic moment of electron manifests itself in the spin-dependent electron scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high-temperature magnetic data of multi-walled carbon nanotube (MWCNT) mat samples embedded with Fe and Fe 3 O 4 nanoparticles Zhao et al (2008) indicated that the room-temperature saturation magnetizations of the magnetic nanoparticles embedded in the MWCNTs are enhanced by a factor of about 3 as compared with what they would be expected to have for free magnetic nanoparticles. Recently, the study has been extended to nickel nanoparticles embedded in MWCNTs Wang et al (2010) and shown a similar enhancement factor. More intriguringly, there were reports of ultrahigh temperature superconducting behaviors in carbon films Antonowicz (1974); Lebedev (2004), carbon nanotubes Zhao & Wang (2001); Zhao (2004;, graphite Kopelevich et al (2000), and graphite-sulfur composites Da Silva et al (2001); Moehlecke et al (2004).…”
Section: Introductionmentioning
confidence: 99%